Tinjauan Teoritis: Self Regulation pada Mahasiswa Underachiever - Francis, Nangoi Priscilla (Bina Nusantara University, 2011)
Self regulation is needed by every individual as a description of their ability to control themselves. Not every individual has good self regulation such as students categorized as underachievers. Self regulation on underachiever students could be said to be lower than high achiever students. There are many factors contributing to low self regulation, such as lack of responsibility towards personal goals, even personal goals that may be set by someone else.This theoretical review is anticipated to help realizing conditions that is happening towards ourselves and what is the factor behind it. Parents and educators may also understand the treatment causing children to have low self regulation and becoming an underachiever.